Effect of Zn2+ co-doping on the luminescence of Sm3+ doped SrMoO4 phosphor - Chauhan V.; Pandey P.K.; Dixit P.; Deshmukh P.; Satapathy S.; Pandey P.C. (My University, 2025)
In this paper, we report the result of Zn2+ co-doping on the photoluminescence and structural properties of Sm3+ doped SrMoO4 phosphors which are synthesized by a lucrative auto combustion method. The structural study ascertains the improvement in crystallinity of the Sm3+ doped SrMoO4 phosphor by Zn2+ co-doping. Photoluminescence excitation analysis evinces that the intensity of 404 nm peak (6H5/2 → 4F7/2) is enhanced by 93.5% after 1% Zn2+ co-doping in the 4% Sm3+ doped SrMoO4 phosphor. Emission study manifests that the intensity of Sm3+ doped SrMoO4 phosphors increases up to 4% doping concentration of Sm3+ ion, and its peaks located at 562 nm, 597 nm, 645 nm, and 705 nm are ascribed to 4G5/2 to 6HJ/2 (J = 5, 7, 9, and 11) electronic transitions of Sm3+ ions, respectively. The overall emission of Sm3+ doped SrMoO4 phosphors lies in the reddish-orange region. The emission intensity of 4% Sm3+ doped SrMoO4 is further increased by 87.80% after 1% Zn2+ co-doping. The lifetime of the 4G5/2 level of the Sm3+ ions has also increased on doping 1% Zn2+ ions. The temperature-dependent emission spectra reveal good thermal stability of the phosphor with 0.17eV activation energy. The prepared Zn2+ co-doped SrMoO4:4Sm3+ phosphor has near-UV excitation and reddish-orange emission and thus can be used as a potential red phosphor in lighting devices. © 2022 Elsevier B.V.